(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
This paper examines the concept of business process reengineering and how it can help organizations transform their operations processes to gain competitive advantage. Business process reengineering involves rethinking and redesigning existing business processes to dramatically improve key performance metrics such as cost, quality, service and speed. The traditional incremental improvement approach is insufficient to cope with today’s rapidly changing business environment. Organizations need to break existing rules and boundaries and think out of the box to change how work is done fundamentally. The paper discusses the principles and approaches of business process reengineering and how it can lead to more efficient, streamlined processes. It also addresses challenges in implementing business process reengineering and critical success factors. Case studies of organizations that have successfully applied business process reengineering to gain significant benefits are presented.